(untitled) (Vietnam Journal of Community Medicine, 2026)
Bleomycin, a Glycopeptide antibiotic, was discovered in 1966 to possess antitumor cytotoxic activity. Its potent tumoricidal properties have secured it a vital role in cancer chemotherapy. While it causes minimal myelosuppression, pulmonary toxicity is a serious and potentially life-threatening adverse effect, occurring in approximately 10% of patients (range 6-18%), with a reported mortality rate of 3-5%. The patterns of lung injury are diverse and include diffuse alveolar damage (DAD), interstitial fibrosis, nonspecific interstitial pneumonia (NSIP), organizing pneumonia (OP), and eosinophilic pneumonia. Pneumothorax and pneumomediastinum are recognized as very rare complications of Bleomycin. Herein, we present a rare case of Bleomycin-induced interstitial pneumonia complicated by spontaneous pneumomediastinum. This case highlights the importance of early recognition, accurate differential diagnosis, and prompt management of this uncommon yet potentially fatal complication.